Religion of the Han Empire : Postmortem Transformation, Immortality, and the Rise of Daoism - JIANG, Sheng, (Asian Studies E-Books Online, Collection 2025., 2025)
By examining the tomb images and artifacts from a religious perspective, combined with a cognitive approach that strives to uncover the essentials of the Han belief system, the author convincingly shows how Han belief represented the dimension of faith in the national power structure while reconstructing the history of religious Daoism at the time. This is the first historical study on the subject using this new methodology.